View of the Issue About Changes in the Age of Marries for Women in Law Number 16 of 2019 - Saiful Saiful (UIN Sunan Gunung Djati Bandung, 2019)
With regard to marriage problems in Indonesia, the age limit of marriage is regulated in positive law contained in Law Number 1 of 1974 and KHI, namely Marriage is only permitted if the male has reached the age of 19 (nineteen) years and the woman has reached the age 16 (sixteen) years, which was later revised in Law Number 16 of 2019 which states that marriage is only permitted if a man and woman have reached the age of 19 (nineteen) years, then if seen from the maslahah concept this determination is at the daruriyyah level, namely maintaining the safety of the soul (hifzu al-nafs), maintaining the safety of the mind (hifzu al-'aql), and maintaining the safety of the offspring (hifzu al-nasl). The change in the minimum age of marriage that occurs in the Marriage Law Article 7 paragraph (1) No. 1 of 1974 contains more maslahah and is more in accordance with maqasid sharia. Because at the age of 19, it is hoped that the ideal marriage can be accomplished and be able to realize the goals of marriage, such as maintaining offspring, creating a sakinah mawaddah wa rahmah family, maintaining lineages, creating patterns of family relationships, maintaining diversity in the family and preparing for economic aspects.